Analisis Kelayakan Usaha Jagung Manis Bakar Dan Rebus Pada Industri Rumah Tangga - Hawurubun, Rati Ningsih; Untari, Untari; Nahumury, Marthen A.I. (MuJAgri: Musamus Journal of Agribusiness, 2020)
The purpose of this study is how much profit rate from the business of roasted and boiled sweet corn and whether the business of roasted and boiled sweet corn is feasible. This research was conducted in Marga Mulya Village, Semangga District, Merauke Regency. Samples of 10 businesses of sweet and roasted sweet corn industry. Data analysis uses cost analysis, revenue, revenue, profitability and business feasibility. The results show a profit level of Rp.5,241,279 / month, so that the roasted and boiled sweet corn business is profitable. Analysis of the R / C feasibility level of 1,360, NPV (Net Present Value) has a value greater than zero, which is Rp. 190,832,954.2 and the Net B / C value ratio (Benefit Cost Ratio) obtained is equal to (1.52) years, so that the business of roasted sweet corn and stew is feasible to be undertaken. Keywords: industry; household; income; appropriateness